Hubungan Pengetahuan Terhadap Sikap Rasionalitas Suplemen Vitamin C Pada Masyarakat Desa Peguyangan Kangin, Denpasar Utara - Kirana, Chandra (Bali International University, 2022)
Knowledge about COVID-19 disease is very important so as not to cause an increase in the number of cases of COVID-19 disease. A total of 30.65% of public knowledge about COVID-19 is still not good. In an effort to increase immunity in the midst of the COVID-19 pandemic, based on the guidelines for the management of COVID-19 Edition 3, consuming vitamin C is one of the pharmacological treatments for COVID-19. No wonder, if many people are competing to buy vitamin C supplements. Purpose: This study aims to determine the relationship between knowledge of COVID-19 and the rationality of vitamin C supplements among the people of Peguyangan Kangin Village, Denpasar Utara. Method: This study is a non-experimental study, with a cross-sectional design. The research time is from March to May 2022. Data analysis using the Spearman Rank test. The sample used in this study were 109people using the Non-Probability Sampling method with purposive sampling technique. With the inclusion criteria that have been determined. Results: This study shows that there is a significant relationship between knowledge of the attitude of rationality of vitamin C as indicated by the P-value of the Spearman Rank test (0.001) < (0.05).Conclusion: There is a significant relationship between public knowledge about COVID-19 on the rationality of vitamin C supplements with the Correlation Coefficient value of 335%.